Oleanolic Acid Enhances the Beneficial Effects of Preconditioning on PC12 Cells - Babongile C. Ndlovu; Willie M. U. Daniels; Musa V. Mabandla (Parkinson's Disease)
Preconditioning triggers endogenous protection against subsequent exposure to higher concentrations of a neurotoxin. In this study, we investigated whether exposure to oleanolic acid (OA) enhances the protective effects of preconditioning on PC12 cells exposed to 6-hydroxydopamine (6-OHDA). A concentration response curve was constructed using 6-OHDA (50, 150, 300, and 600 μM). The experiment consisted of 6 groups: untreated, OA only, Group 1: cells treated with 6-OHDA (50 μM) for 1 hour, Group 2: cells treated with 6-OHDA (150 μM) for 1 hour, Group 3: cells treated with 6-OHDA (50 μM) for 30 minutes followed 6 hours later by treatment with 6-OHDA (150 μM) for 30 minutes, and Group 4: cells treated as in group 3 but also received OA immediately after the second 6-OHDA treatment. Cell viability and apoptotic ratio were assessed using the MTT and Annexin V staining tests, respectively. In preconditioned cells, we found that cell viability remained high following exposure to 6-OHDA (150 μM). OA treatment enhanced the protective effects of preconditioning. Similarly, with the annexin V apoptosis test, preconditioning protected the cell and this was enhanced by OA. Therefore, preexposure of PC12 cells to low 6-OHDA concentration can protect against subsequent toxic insults of 6-OHDA and OA enhances this protection.